Wide bandgap perovskite solar cells and stacked cells, and electrical devices
By using a high-performance organic and inorganic hybrid perovskite material system and anti-solvent method, annealing treatment under anhydrous, oxygen-free and humidity and temperature conditions, the problems of energy loss and high production costs of wide-bandgap perovskite solar cells are solved, and device performance improvement and process simplification are achieved.
Patent Information
- Application Number
- CN202410537981.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Existing wide-bandgap perovskite solar cells have large energy losses, long process time, high production costs, and device performance and production capacity need to be improved.
The high-performance organic and inorganic hybrid perovskite material system is adopted, combined with the anti-solvent method, the intermediate phase annealing and precipitation is carried out under anhydrous and oxygen-free conditions to improve the quality of the intermediate phase; then further annealing is carried out under certain humidity and temperature conditions to improve the quality of the perovskite film and reduce the defect density.
It effectively improves the device performance of wide-bandgap perovskite solar cells, reduces energy loss, shortens process time, reduces production costs, and is conducive to large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of perovskite solar cells, and in particular to a wide bandgap perovskite solar cell, a stacked cell, and an electrical device. Background Art
[0002] Since its introduction in 2009, single-junction perovskite solar cells have been approaching their theoretical Shockley-Queisser (SQ) efficiency limit, and in recent years, they have rapidly achieved a maximum photoelectric conversion efficiency of nearly 26%. In order to further improve the photoelectric conversion efficiency of solar cells, the most promising method is to integrate wide-bandgap (bandgap of 1.68eV) perovskite cells with crystalline silicon cells to construct tandem solar cells. Perovskite cells with a bandgap of 1.68eV are essential for achieving ideal current matching between perovskite cells and crystalline silicon cells in perovskite / crystalline silicon tandem solar cells.
[0003] However, the current wide-bandgap perovskite solar cells with a wavelength of 1.68 eV still face large energy losses, long process times, and high production costs, and the device performance and production capacity need to be further improved. Summary of the invention
[0004] Based on this, the present application provides a wide bandgap perovskite solar cell with better device performance, higher efficiency and low process cost, as well as a stacked cell and an electrical device comprising the wide bandgap perovskite solar cell.
[0005] In a first aspect of the present application, a wide bandgap perovskite solar cell is provided, comprising a first electrode layer, a functional layer and a second electrode layer stacked in sequence, wherein the functional layer comprises a perovskite film, and a method for preparing the perovskite film comprises the following steps:
[0006] applying a precursor solution of an organic-inorganic hybrid perovskite material to a preform, and then adding an anti-solvent to prepare an intermediate part;
[0007] Under the condition of being isolated from water and oxygen, the intermediate piece is subjected to a first annealing at 60° C. to 80° C. to prepare a first piece;
[0008] Under the condition of air environment with humidity less than or equal to 30%RH, the first product is subjected to a second annealing at 90°C-110°C.
[0009] In one embodiment, the first annealing temperature is 65° C. to 75° C.; and / or
[0010] The temperature of the second annealing is 95°C-105°C.
[0011] In one embodiment, the first annealing time is 1 min to 5 min; and / or
[0012] The second annealing time is 8min to 15min.
[0013] In one embodiment, the general structural formula of the organic-inorganic hybrid perovskite material is Cs 0.22 FA 0.78 Pb(I 1-x Br x )3, where x is 0.15~0.2.
[0014] In one embodiment, the steps of applying a precursor solution of an organic-inorganic hybrid perovskite material to a preform and then adding an anti-solvent include:
[0015] The precursor solution is applied to the preform and then subjected to spin coating, and the anti-solvent is added before the spin coating is completed.
[0016] In one embodiment, the spin coating process comprises: a rotation speed of 3000 rpm / min to 5000 rpm / min, a time of 40s to 60s; and / or
[0017] The anti-solvent is added 20s to 35s before the end of the spin coating process.
[0018] In one embodiment, the solvent of the precursor solution includes one or both of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), and the anti-solvent includes one or both of chlorobenzene and anisole.
[0019] In one embodiment, the volume ratio of the anti-solvent to the precursor solution is 5:2-4:1.
[0020] A second aspect of the present application provides a stacked cell, comprising a perovskite cell and a crystalline silicon cell arranged in series, wherein the perovskite cell is the wide bandgap perovskite solar cell described in the first aspect.
[0021] The third aspect of the present application provides an electrical device, comprising the wide bandgap perovskite solar cell described in the first aspect or the stacked cell described in the second aspect.
[0022] The above-mentioned wide bandgap perovskite solar cell is based on a high-performance organic-inorganic hybrid perovskite material system, combined with the anti-solvent method, and the precipitation of the intermediate phase under water-free and oxygen-free conditions, which can effectively improve the quality of the intermediate phase, and then further anneal under certain humidity and temperature conditions, which can effectively improve the quality of the wide bandgap perovskite film, reduce the defect density, and improve the device performance. At the same time, the perovskite film preparation process is short in time, high in production efficiency, and low in cost, which is conducive to large-scale production. DETAILED DESCRIPTION
[0023] The wide bandgap perovskite solar cell, stacked cell, and electrical device of the present application are further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0025] The optional scope of the terms "and / or", "or / and", and "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, said any and all combinations include any combination of any two related listed items, any more related listed items, or all related listed items.
[0026] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.
[0027] In this application, "first aspect", "second aspect", "third aspect", "fourth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0028] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0029] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0030] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0031] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0032] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0033] The room temperature in this application generally refers to 4°C~30°C, preferably 20±5°C.
[0034] At present, wide bandgap perovskite solar cells with a wavelength of 1.68 eV face large energy losses, which is mainly related to the presence of more deep-level defects in low-quality wide bandgap perovskite films, resulting in more serious non-radiative recombination losses. Therefore, effective methods are urgently needed to reduce the energy loss of wide bandgap perovskite films. In addition, in order to obtain high-quality wide bandgap perovskite films in traditional methods, a longer crystallization time (usually about 30 minutes) is usually required, which makes the process time of wide bandgap perovskite solar cells longer, the production cost is relatively high, and the production capacity is low, which is not conducive to large-scale output.
[0035] Based on this, some examples of the present application provide a wide bandgap perovskite solar cell, comprising a first electrode layer, a functional layer, and a second electrode layer stacked in sequence, wherein the functional layer comprises a perovskite film, and a method for preparing the perovskite film comprises the following steps:
[0036] applying a precursor solution of an organic-inorganic hybrid perovskite material to a preform, and then adding an anti-solvent to prepare an intermediate part;
[0037] Under the condition of being isolated from water and oxygen, the intermediate piece is subjected to a first annealing at 60° C. to 80° C. to prepare a first piece;
[0038] Under the condition of air environment with humidity less than or equal to 30%RH, the first product is subjected to a second annealing at 90°C-110°C.
[0039] The above-mentioned wide bandgap perovskite solar cell is based on a high-performance organic-inorganic hybrid perovskite material system, combined with an anti-solvent method, and annealing and precipitation of the intermediate phase under water-free and oxygen-free conditions. While removing the solvent in the intermediate phase, it can also effectively improve the quality of the intermediate phase, and then further annealing under certain humidity and temperature conditions. The humidity in the atmosphere can promote the vaporization of hygroscopic components during thermal annealing, which helps to stabilize the photoactive α-phase perovskite structure, and the oxygen in the air can passivate the defects of the perovskite film during annealing in a low humidity environment, effectively improving the quality of the wide bandgap perovskite film, reducing the defect density, and improving the device performance. At the same time, the perovskite film preparation process has a short time, high production efficiency, and low cost, which is conducive to large-scale production.
[0040] It can be understood that the "preform" refers to the intermediate product of the perovskite solar cell that has been prepared before the perovskite film is prepared, for example, including a first electrode layer (such as ITO glass) and a hole transport layer (such as [2-(3,6-dimethoxy-9-hydrogen-carbazole-9-yl)ethyl]phosphoric acid, MeO-2PACZ) stacked in sequence. After the perovskite film is prepared on the surface of the hole transport layer according to the steps described above, an electron transport layer (such as C 60 ), a hole blocking layer (such as BCP) and a second electrode layer (such as Ag).
[0041] Specifically, during the first annealing, the temperature includes, but is not limited to, 60°C, 62°C, 64°C, 65°C, 66°C, 68°C, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C, 80°C, or a range between any two of the foregoing. Further, the temperature of the first annealing is 65°C to 75°C.
[0042] In some examples, the first annealing time is 1 min to 5 min. Specifically, the first annealing time includes but is not limited to: 1 min, 2 min, 3 min, 4 min, 5 min or a range between any two of the foregoing.
[0043] Specifically, during the second annealing, the temperature includes but is not limited to: 90°C, 92°C, 94°C, 95°C, 96°C, 98°C, 100°C, 102°C, 104°C, 105°C, 106°C, 108°C, 110°C or a range between any two of the foregoing. Further, the temperature of the second annealing is 95°C-105°C.
[0044] In some examples, the second annealing time is 8 min to 15 min. Specifically, the second annealing time includes but is not limited to: 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or a range between any two of the foregoing.
[0045] In some of the examples, during the second annealing process, the humidity includes, but is not limited to, 5%RH, 10%RH, 15%RH, 18%RH, 20%RH, 22%RH, 25%RH, 30%RH, or a range between any two of the foregoing.
[0046] In addition, in some of the examples, the general structural formula of the organic-inorganic hybrid perovskite material is Cs 0.22 FA 0.78 Pb(I 1-x Br x )3, where x is 0.15~0.2.
[0047] In some of these examples, the steps of applying a precursor solution of an organic-inorganic hybrid perovskite material to a preform and then adding an antisolvent include:
[0048] The precursor solution is applied to the preform and then subjected to spin coating, and the anti-solvent is added before the spin coating is completed.
[0049] In some examples, the conditions of the spin coating process include: a rotation speed of 3000 rpm / min to 5000 rpm / min, and a time of 40s to 60s. Specifically, the rotation speed includes but is not limited to: 3000 rpm / min, 3500 rpm / min, 4000 rpm / min, 4500 rpm / min, 5000 rpm / min, or a range between any two of the foregoing. The time includes but is not limited to: 40s, 45s, 50s, 55s, 60s, or a range between any two of the foregoing.
[0050] In some examples, the anti-solvent is added 20s to 35s before the end of the spin coating process. Specifically, the anti-solvent is added 20s, 25s, 28s, 30s, 32s or 35s before the end of the spin coating process.
[0051] In some examples, the solvent of the precursor solution includes one or both of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF). Further, the solvent of the precursor solution includes a combination of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), and the volume ratio of the two can be 1:3~1:4.
[0052] In some examples, the anti-solvent includes one or both of chlorobenzene and anisole. When a combination of chlorobenzene and anisole is used, the ratio of the two can be optional.
[0053] In some examples, the volume ratio of the antisolvent to the precursor solution is 5:2 to 4:1. Specifically, the volume ratio of the antisolvent to the precursor solution includes but is not limited to: 5:2, 3:1, 3.5:1, 4:1 or a range between any two of the foregoing.
[0054] Some other examples of the present application provide a stacked cell, including a perovskite cell and a crystalline silicon cell arranged in series, wherein the perovskite cell is a wide bandgap perovskite solar cell as described above.
[0055] Some other examples of the present application provide an electrical device, comprising the wide bandgap perovskite solar cell as described above or the tandem cell as described above.
[0056] For experimental parameters not specified in the following specific embodiments, reference is made to the instructions given in the present application document, and reference may also be made to experimental manuals in the art or other experimental methods known in the art, or to experimental conditions recommended by manufacturers.
[0057] The raw materials and reagents involved in the following specific examples can be obtained from commercial sources, or can be prepared by those skilled in the art according to known methods.
[0058] Example 1
[0059] This embodiment is a wide bandgap perovskite solar cell, and its preparation steps are as follows:
[0060] 1) ITO glass cleaning preparation: Clean the transparent conductive substrate (ITO glass) with deionized water, acetone and isopropanol for 15 minutes each; after cleaning, blow dry the substrate with a nitrogen gun and place it in a UV ozone cleaner for 20 minutes. After cleaning, place it in a container and transfer it to the glove box for standby use;
[0061] 2) Preparation of hole transport layer: In a glove box, take a certain amount of prepared hole transport layer solution (MeO-2PACz, concentration is 1.5 mg / mL, solvent is methanol), drop it on the substrate and perform spin coating. After the spin coating is completed, place the substrate on a hot stage and anneal and crystallize at a constant temperature. After the crystallization is completed, cool it to room temperature for use;
[0062] 3) Preparation of perovskite film:
[0063] Organic-inorganic hybrid perovskite material Cs 0.22 FA 0.78 Pb(I 1-x Br x)3 (x is 0.2) to prepare a precursor solution, the solvent is a mixed solvent of DMSO and DMF (volume ratio is 1:3); the precursor solution is dripped onto the surface of the hole transport layer, and spin-coated at a speed of 4000rpm / min for 50s, and about 30s before the end of the spin-coating process, 150μL of anti-solvent (type is chlorobenzene, and the volume ratio with the spin-coated precursor solution is 3:1) is quickly dripped at a height of 1cm, and then the spin coating is continued to be completed to prepare the intermediate; the intermediate is first placed in a water-free and oxygen-free glove box, annealed at 70℃ for 2min, and then immediately transferred out of the glove box, and continued to anneal at 100℃ for 10min in a humidity of 25%RH and air environment to prepare a wide bandgap perovskite film, which is cooled to room temperature for use;
[0064] 4) Preparation of electron transport layer: Based on the prepared perovskite film, transfer it into the thermal evaporation chamber and evacuate it until the vacuum degree reaches 10 -4 After the film was below Pa, a 25 nm thick C was deposited at a rate of 0.2 A / s. 60 Thin film, complete the preparation of electron transport layer;
[0065] 5) Preparation of hole blocking layer: After evaporation of C 60 After that, at vacuum degree 10 -4 The BCP film with a thickness of 8 nm was continuously deposited at a rate of 0.2 A / s in the chamber below Pa;
[0066] 6) Preparation of the second electrode layer: After the BCP is deposited, -4 A 100 nm thick metal Ag film was deposited at a rate of 1.4 A / s in a chamber below Pa.
[0067] Example 2
[0068] This embodiment is a wide bandgap perovskite solar cell, and its preparation steps are the same as those in Embodiment 1, with the main difference being that the temperature of the first annealing is 60° C. and the time is 5 min.
[0069] Example 3
[0070] This embodiment is a wide bandgap perovskite solar cell, and its preparation steps are the same as those in Embodiment 1, with the main difference being that the temperature of the second annealing is 110° C. and the time is 8 min.
[0071] Example 4
[0072] This embodiment is a wide bandgap perovskite solar cell, and its preparation steps are the same as those in Embodiment 1, with the main difference being that during the second annealing, the humidity is 10% RH.
[0073] Comparative Example 1
[0074] This comparative example is a wide bandgap perovskite solar cell, and its preparation steps are the same as those of Example 1, with the main difference being that the temperature of the first annealing is 40° C. and the time is 4 minutes.
[0075] Comparative Example 2
[0076] This comparative example is a wide bandgap perovskite solar cell, and its preparation steps are the same as those of Example 1, with the main difference being that the temperature of the second annealing is 120° C. and the time is 10 min.
[0077] Comparative Example 3
[0078] This comparative example is a wide bandgap perovskite solar cell, and its preparation steps are the same as those in Example 1, with the main difference that: both annealings are performed in a water-free and oxygen-free glove box. The specific steps are: placing the intermediate piece in a water-free and oxygen-free glove box, annealing at 100°C for 30 minutes, and preparing a wide bandgap perovskite film.
[0079] Test example:
[0080] Test method: Tested in a glove box, the glove box temperature is about 25℃, the water and oxygen content is less than 0.01ppm, the battery device JV curve is tested by Keithley 2400 source meter, the light source is AM1.5G, 100mW / cm 2 ,The light source intensity is calibrated by a standard silicon battery, the voltage test range is -0.1V-1.3V, the step size is 0.01V, and the delay time is 50ms.
[0081] The test results are shown in Table 1 below:
[0082] Table 1
[0083]
[0084] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0085] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the patent application. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A wide bandgap perovskite solar cell, characterized in that: The invention comprises a first electrode layer, a functional layer and a second electrode layer stacked in sequence, wherein the functional layer comprises a perovskite film, and the preparation method of the perovskite film comprises the following steps: According to the organic-inorganic hybrid perovskite material Cs 0.22 FA 0.78 Pb(I 1-x Br x )3. x is 0.2 to prepare a precursor solution, and the solvent is a mixed solvent of DMSO and DMF in a volume ratio of 1:3; The precursor solution is applied to the preform, and the preform is spin-coated at a speed of 4000 rpm for 50 seconds. About 30 seconds before the end of the spin coating process, 150 μL of anti-solvent is added dropwise at a height of 1 cm, wherein the anti-solvent is chlorobenzene, and the volume ratio of the anti-solvent to the spin-coated precursor solution is 3:1, and then the spin coating is continued to complete to prepare the intermediate part; The intermediate piece was first placed in a water-free and oxygen-free glove box and annealed at 70° C. for 2 min. Then, it was transferred out of the glove box and further annealed at 100° C. for 10 min in an air environment with a humidity of 25% RH to prepare a perovskite film.
2. A laminated battery, characterized in that: It comprises a perovskite cell and a crystalline silicon cell arranged in series, and the perovskite cell is the wide bandgap perovskite solar cell according to claim 1.
3. An electrical device, characterized in that: It includes the wide bandgap perovskite solar cell according to claim 1 or the stacked cell according to claim 2.
Citation Information
Patent Citations
Multi-junction device production process
CN113228323A
A method of forming a light absorbing perovskite layer for a photovoltaic cell and a photovoltaic cell comprising the light absorbing perovskite layer
WO2018068101A1